RELIGIOUS ATTITUDES OF THEOLOGICAL TRADISIONALIST IN THE MODERN MUSLIM COMMUNITY: Study on Tahlilan in Kotagede (State Islamic University (UIN) of Sunan Ampel Surabaya, 2016)
In modernist Islamic thoughts, anything that comes from tradition, and that does not have any justiable ground in the Islamic law, must be abandoned since it is considered as heresy. However, a totally opposite situation occurs in Kotagede. Tahlilan, one of those forbidden traditions, has been widely practiced by modernist Muslims. This paper attempts to examine the religious behavior of modernist community in Yogyakarta, especially with regard to motives and functions of their participation in tahlilan. Using Emil Durkheim's sociological approaches, namely social solidarity and functionalism, the research result shows that the tradition of tahlilan remains present amongst the modernist Muslim society in Kotagede due to three factors, these are, because of tolerance values and accommodative attitudes that they hold, the cultural aspects passed on from generation to generation, and the social needs. These three aspects can incorporate in each individual, and sometimes are only partially. It depends on the value system adopted by each individual. Furthermore, maintaining social role and status also becomes another factor that the tradition of tahlilan could be kept alive and preserved until now.